Sistem-Mekanisme Promosi Novel Chicklit dan Teenlit Indonesia - Redyanto Noor (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
In the context of promotion there are interesting phenomena related to the process of traveling chicklit and teenlit novels since going out from the publisher's warehouse to the readers. The process is through systems and mechanisms that involve many professional workers outside the field of literature. They are the marketing profession; from a public-relation, sales-promotion, to event organizers. To spread the chicklit and teenlit novels, team-work utilizes mass psychology conditions. The potential for public consumerism is exploited through various strategies. Every major publisher such as Elex Media Komputindo, GagasMedia, and Gramedia Pustaka Utama, has a promotion and marketing division that is responsible for selling products and ensuring the smooth distribution of products to consumers in the broadest range of regions. This business involves professional workers in certain fields that work in synergy. Promotional tips are carried out through event launching, book launching, book reviews,